2021
DOI: 10.21203/rs.3.rs-690608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monocyte Distribution Width As A Novel Sepsis Indicator in COVID-19 Patients

Abstract: Background The severe acute respiratory syndrome coronavirus (SARS-CoV-2) is a highly transmittable virus which causes the novel coronavirus disease (COVID-19). Monocyte distribution width (MDW) is an in-vitro hematological parameter which describes the changes in monocyte size distribution and can indicate progression from localized infection to systemic infection. In this study we evaluated the correlation between the laboratory parameters and available clinical data in different quartiles of MDW to predict… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…We further compared these in vitro modifications to those measured in COVID-19 and Sepsis patients. The cut-offs reported for both MDW index and histone values are in agreement with literature references (healthy control subjects [5,6,11,12,15]; COVID-19 patients [12,14,15]; and Sepsis patients [5,6,11]).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We further compared these in vitro modifications to those measured in COVID-19 and Sepsis patients. The cut-offs reported for both MDW index and histone values are in agreement with literature references (healthy control subjects [5,6,11,12,15]; COVID-19 patients [12,14,15]; and Sepsis patients [5,6,11]).…”
Section: Introductionsupporting
confidence: 89%
“…Among common laboratory biomarkers shared by SARS-CoV-2 and Sepsis infections [7,11], the modification of the hematological parameter Monocyte Distribution Width (MDW) predicts both multiorgan failure and increased mortality rate in Sepsis conditions [11]. MDW index (FDA-approved, EC-marked early Sepsis indicator of monocyte heterogeneity upon massive inflammatory activation [11]) is further recognized as diagnostic/prognostic marker for COVID-19 severity and clinical outcomes, as a kind of novel viral Sepsis biomarker [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Riva et al reported a signi cant positive correlation between MDW and in ammatory markers such as CRP, brinogen, and ferritin in COVID-19 patients[6]. Alsuwadi revealed that high MDW value (> 24.6) had a strong correlation with poor prognosis COVID-19 biomarkers[7]. Similar to previous studies, CRP was elevated in patients with SARS-CoV-2 infection and statistically signi cant higher in the respiratory support group.…”
supporting
confidence: 68%
“…The value of MDW as a diagnostic tool has been investigated in sepsis and coronavirus disease (COVID-19). [1][2][3][4][5][6][7][8][9][10][11] Increased MDW values are associated with both disorders; however, the mechanistic processes that underpin these observations remain less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte distribution width (MDW) is a parameter generated alongside full blood counts (FBC) in new generation haematology analysers. The value of MDW as a diagnostic tool has been investigated in sepsis and coronavirus disease (COVID‐19) 1–11 . Increased MDW values are associated with both disorders; however, the mechanistic processes that underpin these observations remain less clearly defined.…”
Section: Introductionmentioning
confidence: 99%